Analysis and design of wireless power delivery system for biomedical implants - Low, Geng Hong. (2013)
The development of wireless power technology for biomedical implant application has accelerated over the past years due to its potential in reducing surgeries to change the internal battery for biomedical implant patients. Lesser surgeries will translate to lesser surgical risk to undertake and more time and money saved.